(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A prominent public figure’s suicide frequently generates significant and spectacular media coverage. There are always worries over whether or not such reporting influences future suicides. Regarding imitative suicides, Durkheim, Lester, Phillips, and other academics have divergent opinions. Numerous fragments of anecdotal evidence, research, and meta-analyses have already proven the media’s representation of suicide as an independent risk factor for additional suicides in society. This phenomena was dubbed the "Werther effect" by Philips, after the protagonist of Goethe’s masterpiece "The Sorrows of Young Werther." In this paper, we examine the Werther effect, its hypothesised mechanism, some statistical considerations, the at-risk population, and key variables associated with this phenomena, as well as new media guidelines.